2014
DOI: 10.1017/s1049023x14000971
|View full text |Cite
|
Sign up to set email alerts
|

Formula One Night Race in Singapore: A 4-Year Analysis of a Planned Mass Gathering

Abstract: Musculoskeletal conditions and heat-related illnesses were the most common presenting complaints at the Singapore Grand Prix from 2009-2012. The lack of correlation between heat index and PPR is a new finding compared with prior studies. This could be due to the minimal heat variation that occurred during the night event. Further study is required to refine models that can be used in specialized events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…When compared with a larger study that described a similar event (ie, F1GP in Singapore), we obtained comparable results regarding the type of disease leading the patients to request medical assistance. 8 Despite the peak of intervention on Sunday, which was strongly related to the higher number of attendances, the number and the type of resources implemented could be considered adequate due to the almost negligible impact on the local hospitals. The daily average of patients admitted to the emergency department of San Gerardo Hospital (the referral hospital of Monza and the entire district) by EMS service is 36.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with a larger study that described a similar event (ie, F1GP in Singapore), we obtained comparable results regarding the type of disease leading the patients to request medical assistance. 8 Despite the peak of intervention on Sunday, which was strongly related to the higher number of attendances, the number and the type of resources implemented could be considered adequate due to the almost negligible impact on the local hospitals. The daily average of patients admitted to the emergency department of San Gerardo Hospital (the referral hospital of Monza and the entire district) by EMS service is 36.…”
Section: Discussionmentioning
confidence: 99%
“…8 In this study, the PPR was calculated as 4.4 and the TTHR was calculated as 0.58. In a study performed in Singapore Formula One Races, the PPR was calculated as 2.17 and the TTHR was calculated as 0.033; 7 and in a music festival, the PPR was found as 4.09. 9 Causes of these rates being higher in this study were associated with an open area that found people from all age groups under rough terrain, like Arbon indicated.…”
Section: Discussionmentioning
confidence: 99%
“…The data obtained from medical forms and reports from the ceremonies were yielded descriptive statistics by transferring to SPSS 19.0 statistical package program (IBM; Armonk, New York USA). Furthermore, the patient presentation rate (PPR) was obtained by dividing the number of patients/injured persons admitted to the medical services into the number of total participants and multiplying the resulting number by 1,000; the transport to hospital rate (TTHR) was calculated by dividing the number of patients transferred from the region to the closest hospital into the number of participants overall and multiplying the resulting number by 1,000; 2 , 7 and the pre-diagnosis rate (PDR) was calculated by dividing the number of certain pre-diagnosis of patients/injured persons into the number of participants overall and multiplying the resulting number by 1,000 8 …”
Section: Methodsmentioning
confidence: 99%
“…[ 21 ] In Formula 1 Singapore Night Races, PPR was found to be 2.7, and Transport to Hospital Rate was 0.034. [ 22 ] The majority of applications/admissions (%58.7) in races are musculoskeletal injuries which include fluid retention, lacerations, abrasions, sprains, and strains. [ 22 ] In the study, the average temperature was calculated as 31.8°C and the average relative humidity was 93.8%, while the temperature index 50.3°C.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] The majority of applications/admissions (%58.7) in races are musculoskeletal injuries which include fluid retention, lacerations, abrasions, sprains, and strains. [ 22 ] In the study, the average temperature was calculated as 31.8°C and the average relative humidity was 93.8%, while the temperature index 50.3°C. [ 22 ] The temperature-related applications are seen to be over 19%.…”
Section: Introductionmentioning
confidence: 99%